Simultaneous ionization and analysis of 84 anabolic androgenic steroids in human urine using liquid chromatography‐silver ion coordination ionspray/triple‐quadrupole mass spectrometry. Issue 11 (9th November 2014) - Kim, So‐Hee; Cha, Eun‐Ju; Lee, Kang Mi; Kim, Ho Jun; Kwon, Oh‐Seung; Lee, Jaeick
<x xml:space="preserve">Abstract</x> Metal ion coordination ionspray (M+CIS) ionization is a powerful technique to enhance ionization efficiency and sensitivity. In this study, we developed and validated an analytical method for simultaneous ionization and analysis of 84 anabolic androgenic steroids (65 exogenous and 19 endogenous) using liquid chromatography‐silver ion coordination ionspray/triple‐quadrupole mass spectrometry (LC‐Ag+CIS/MS/MS). The concentrations of silver ions and organic solvents have been optimized to increase the amount of silver ion coordinated complexes. A combination of 25 μM of silver ions and methanol showed the best sensitivity. The validation results showed the intra‐ (0.8–9.2%) and inter‐day (2.5–14.9%) precisions, limits of detection (0.0005–5.0 ng/mL), and matrix effect (71.8–100.3%) for the screening analysis. No significant ion suppression was observed. In addition, this method was successfully applied to analysis of positive samples from suspected abusers and useful for the detection of the trace levels of anabolic steroids in human urine samples. Copyright © 2014 John Wiley & Sons, Ltd.